2002
DOI: 10.1063/1.1514660
|View full text |Cite
|
Sign up to set email alerts
|

A linear approach for the evolution of coherent structures in shallow mixing layers

Abstract: The development of large coherent structures in a shallow mixing layer is analyzed. The results are validated with experimental data obtained from particle tracking velocimetry. The mean flow field is modeled using the self-similarity of the velocity profiles. The characteristic features of the down-stream development of a shallow mixing layer flow, like the decrease of the velocity difference over the mixing layer, the decreasing growth of the mixing layer width, and the transverse shift of the center of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 14 publications
6
101
0
Order By: Relevance
“…Shallow flow phenomena can be found in rivers, coastal zones or the atmosphere, where the dominating processes are two-dimensional [1]. Large coherent motions, that are inititated, for instance, in shallow wake flows behind obstacles [2] or in shallow mixing layers [3][4][5] strongly influence the dynamics of such a system and are, therefore, a determining factor for the mixing and transport processes. Measurement of the velocity field describing the generation and the evolution of these coherent motions is the major aim of this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Shallow flow phenomena can be found in rivers, coastal zones or the atmosphere, where the dominating processes are two-dimensional [1]. Large coherent motions, that are inititated, for instance, in shallow wake flows behind obstacles [2] or in shallow mixing layers [3][4][5] strongly influence the dynamics of such a system and are, therefore, a determining factor for the mixing and transport processes. Measurement of the velocity field describing the generation and the evolution of these coherent motions is the major aim of this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…It should be also pointed out that the base flow used in the paper is obtained from averaged long-term evolution of the flow, so that it includes nonlinear effects and changes in the initial structure of the mixing layer. However, such an approach is used earlier in the literature [8] and found to be useful in characterizing the development of coherent structures (at least at the initial stage). More detailed parametric study is needed in order to fully assess the effect of asymmetry of the base flow on the stability characteristics of shallow mixing layers.…”
Section: Methodsmentioning
confidence: 99%
“…[34]. The arrows indicate the mean streamwise velocity 1.2 Linear behaviour of unstable flows in a shallow mixing layer A study by [33] has revealed that the spectral distribution of the large scale motions of a shallow mixing layer can be predicted from a linear stability analysis. First, the mean flow was predicted, based on the self-similarity method proposed by [5].…”
Section: The Shallow Mixing Layermentioning
confidence: 99%
“…This implies also that the intensity level from which the Values measured at the free-surface (dots) are compared with a prediction derived from a linear stability analysis (lines). The straight horizontal line represents the uniform energy level imposed at the inflow [33] structures start to grow are of key importance for their strength. The turbulence properties of the ambient flow therefore play an important role in the energy transfer between the turbulent scales in the mixing layer and should thus be accounted for.…”
Section: The Shallow Mixing Layermentioning
confidence: 99%
See 1 more Smart Citation